Inversion of speech by non-linear transformation of temporary - Wielgat, Robert; Lorenc, Anita (Health Promotion & Physical Activity, 2016)
Electromagnetic Articulography (EMA) is a precise method for speech articulators assessment which is carried out by sensors placed mainly on the tongue. Various methods are being developed in order to avoid the assessment by EMA sensors. One of them is speech inversion. Here preliminary research on speech inversion based on dynamic time warping (DTW) method has been described. Mel-frequency cepstral coefficients (MFCC) method has been chosen as the acoustic speech signal parametrization method. Root mean square errors (RMSE) of the evaluation have been presented and discussed.